2017
DOI: 10.1016/j.brq.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Industry specific financial distress modeling

Abstract: This study investigates uncertainty levels of various industries and tries to determine financial ratios having the greatest information content in determining the set of industry characteristics. It then uses these ratios to develop industry specific financial distress models. First, we employ factor analysis to determine the set of ratios that are most informative in specified industries. Second, we use a method based on the concept of entropy to measure the level of uncertainty in industries and also to sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 48 publications
(66 reference statements)
0
27
0
8
Order By: Relevance
“…In addition to accounting ratios, market variables are also used in an ex-ante model as they contain information on expected future cash flows, which are relevant to the likelihood of being financial distressed (Rees, 1995 A literature review shows that there is a great number of predictors that can be utilized in a financial distress prediction model. According to Zhou et al (2012), there are 500 different variables that can be found in 128 papers and the predictive power of each variable changes in different papers (Sayari & Mugan, 2016). As stated by Powell (2007), the high dimensionality problem can be raised if too many variables are used for data analysis.…”
Section: Review Of Predictors and Predictor Selectionmentioning
confidence: 99%
“…In addition to accounting ratios, market variables are also used in an ex-ante model as they contain information on expected future cash flows, which are relevant to the likelihood of being financial distressed (Rees, 1995 A literature review shows that there is a great number of predictors that can be utilized in a financial distress prediction model. According to Zhou et al (2012), there are 500 different variables that can be found in 128 papers and the predictive power of each variable changes in different papers (Sayari & Mugan, 2016). As stated by Powell (2007), the high dimensionality problem can be raised if too many variables are used for data analysis.…”
Section: Review Of Predictors and Predictor Selectionmentioning
confidence: 99%
“…Ohlson (1980) derives a bankruptcy prediction model as an alternative to Altman' s Z score model. The study employs logistic regression to examine the probability of a firm being bankrupt or non-bankrupt for the period of 1970 -1976 (Sayari, Naz and Can Simga Mugan, 2017). The Ohlson model is different from the previous study model because this model has 9 variables consisting of several financial ratios.…”
Section: Ohlson' S Modelmentioning
confidence: 99%
“…Dengan mengunakan model ini, maka gejal satau ancaman kesulitan keuangan secara dini dapat diketahui sehingga dapat dilakukan upaya-upaya perbaikan sebelum kondisi perusahaan berada dalam kondisi krisis. (Sayari & Simga, 2017).…”
Section: Pendahuluanunclassified